Education and training of clinical research professionals and the evolution of the Joint Task Force for Clinical Trial Competency - Sonstein, Stephen A.; Silva, Honorio; Jones, Carolynn T.; Bierer, Barbara E. (Frontiers in Pharmacology, 2024)
Clinical research professionals play a critical role in the design, conduct, and oversight of clinical trials, and they must have the knowledge, skills, and abilities to ensure that trials are conducted ethically, safely, and in accordance with regulatory requirements. As clinical research has evolved from being a necessary activity for the development and regulatory approval of new medicines to an accredited academic discipline and more recently to a globally recognized profession, the methods of education and training of professionals have also evolved. Initially, on-the-job informal coaching and specialized training organizations led to formalized and accredited academic degree programs and, more recently, to international competency standards and competency maintenance through continuing professional development. The Joint Task Force for Clinical Trial Competency (JTF) is a multidisciplinary, international group of experts that came together to aggregate and refine competency standards for clinical research professionals, first published in 2014. The eight domains and 49 specific core competencies of the JTF Framework have become a globally recognized standard upon which education and training programs, role descriptions, and upward mobility criteria for professionals are now based. The JTF meets regularly and through its workgroups continues to evolve in response to the changing needs of the profession. The JTF is committed to continuous improvement to ensure that clinical research professionals have the competence necessary to conduct safe, ethical, and high-quality clinical research.